New arrangement of three genera of fish tapeworms (Cestoda: Proteocephalidae) in catfishes (Siluriformes) from the Neotropical Region: taxonomic implications of molecular phylogenetic analyses - Alves, Philippe V; de Chambrier, Alain; Luque, José L; Takemoto, Ricardo M; Tavares, Luiz E R; Scholz, Tomáš (Parasitology research, 2021)
Tapeworms (Cestoda: Proteocephalidae) are the dominant component of communities of intestinal parasites in pimelodid and other catfishes (Siluriformes) from South America. Even though these parasites have been studied intensively over more than one century, molecular taxonomy and phylogenetics have questioned their morphology-based classification, thus raising doubts about the systematic value of traits commonly used to circumscribe individual taxa. In the present study, members of three morphologically well-characterized genera of proteocephalids from pimelodid (Hemisorubim platyrhynchos and Sorubim lima) and auchenipterid (Ageneiosus inermis) catfishes from the Paraná or Amazon River basins were subjected to DNA sequencing of the large subunit nuclear ribosomal RNA (lsrDNA) and complete mitochondrial cytochrome c oxidase subunit I (COI). Phylogenetic analyses revealed the sister relationship between Manaosia bracodemoca and Mariauxiella piscatorum, and among Mariauxiella pimelodi and Ageneiella brevifilis. As a result, Mar. piscatorum and A. brevifilis are transferred to Manaosia and Mariauxiella, respectively, as Manaosia piscatorum n. comb. and Mariauxiella brevifilis n. comb., and the genus Ageneiella is suppressed. Diagnoses of Manaosia and Mariauxiella are amended. In addition, the present study revealed misidentification of tapeworms whose sequences are deposited in the GenBank database.
Keywords: Cestoda; COI; Catfishes; řeky; Phylogeny; Cestodes; Molecular systematics; Neotropical Region; lsrDNA; Fish Diseases; fylogeneze; Animals; sumci; Jižní Amerika; Rivers; zvířata; nemoci ryb; South America